1993
DOI: 10.4269/ajtmh.1993.48.748
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Morbidity Among Children Exposed to Low Seasonal Transmission in Dakar, Senegal and its Implications for Malaria Control in Tropical Africa

Abstract: To measure morbidity due to malaria and to study its relationship with transmission and parasitemia in children living in an area of low malaria endemicity, a cohort study of 343 schoolchildren was undertaken during a one-year period in Dakar, Senegal. From parallel investigations on transmission and the frequency of malana as a cause for outpatient visits, three different seasons were chosen for close monitoring of different clinical, parasitologic, and Sero-immunologic parameters. The daily incidence rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
1
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 7 publications
4
40
1
4
Order By: Relevance
“…Although P. vivax malaria is generally regarded as benign, it may produce considerable global mortality through malnutrition (8) and may be responsible for a large share of student absences from school (9). The fact that this study found no discernible difference in malaria incidence between the genders reinforces the hypothesis of indoor transmission; a higher incidence among males would have suggested outdoor transmission.…”
Section: Discussionsupporting
confidence: 53%
“…Although P. vivax malaria is generally regarded as benign, it may produce considerable global mortality through malnutrition (8) and may be responsible for a large share of student absences from school (9). The fact that this study found no discernible difference in malaria incidence between the genders reinforces the hypothesis of indoor transmission; a higher incidence among males would have suggested outdoor transmission.…”
Section: Discussionsupporting
confidence: 53%
“…M orbidity results concerning during the followup of this cohort are quite similar to previous studies in different areas of Senegal (Trape et al, 1987(Trape et al, , 1993. The most interesting results concern the treatment strategy used in this context considering the availability of all drugs at the health facility, and the free access to health centers for the population.…”
Section: Discussionsupporting
confidence: 83%
“…En Quibdó, como en áreas urbanas de África, diversos factores podrían contribuir a la presencia de focos de malaria en zonas periurbanas, tales como la urbanización poco planeada, la deficiencia en la infraestructura de vivienda (10), la carencia de servicios públicos, el bajo nivel socioeconómico de la población que habita en los límites de la ciudad (11) y la cercanía de las casas a campos irrigados y en general a cuerpos de agua y territorios ricos en vegetación en donde posiblemente la disponibilidad de criaderos es mayor (12,13) . En contraste, las zonas altamente urbanizadas del centro de la ciudad con casas de concreto y sin vegetación presentan las incidencias más bajas y son negativas para criaderos (Freddy Córdoba, Programa de Control de Malaria Quibdó; comunicación personal) (11).…”
Section: Discussionunclassified